Standard Manufacturing Procedure of Kumaryasva Prepared From Aloe Vera - Sharma, Vinay (International Journal of Pharmaceutical & Biological Archive, 2013)
Standard Manufacturing Procedure of Kumaryasva Prepared From Aloe Vera